Comparative characterization of oxidative stress in cervical cancer at different clinical stages of disease - I. I. Antoneeva; T. P. Gening; D. R. Arslanova; E. G. Sidorenko (Опухоли женской репродуктивной системы)
Parameters of oxidative stress on the level of malondialdehyde (MDA), activity of glutathione-reductase, glutathione-transferase, superoxide- dismutase (SOD) and catalase in tumor tissue, plasma and red blood cells of patients with cervical cancer (CC) w as evaluated a t various clinical stages of the disease. It is revealed that an increase in tumor tissue MD A and glutathione enzymes while reducing SOD and catalase, which may indicate the development of oxidative stress in the dynamics of tumor progression. The data obtained suggest the increase of expres- sion of oxidative stress in red blood cells and tumor tissue in CC in the dynamics of tumor progression.